2013
DOI: 10.1111/jam.12147
|View full text |Cite
|
Sign up to set email alerts
|

Continued widespread dissemination and increased poultry host fitness of Campylobacter jejuni ST-4526 and ST-4253 in Japan

Abstract: Aims: Campylobacter jejuni is a major cause of foodborne gastroenteritis. We previously reported the widespread Camp. jejuni sequence type ( Significance and Impact of the study: This is the first evidence of the continued thriving of ST-4526/ST-4253 in Japan with their increased in vivo fitness. Our findings suggest that poultry mediates the microevolution of this pathogen, thereby enabling these STs to become widespread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 35 publications
0
29
3
Order By: Relevance
“…The reasons for the high prevalence (9/46 isolates [19.6%]) of ST-21 isolated from ducks in our study may be that ducks are an ST-21 host and that no large investigations have compared data for ducks with those for other poultry, such as chickens and turkeys, from the MLST database. The increasing fitness of certain STs may have induced the high prevalence in ducks, as poultry may mediate the microevolution of Campylobacter to become widespread (45). Ducks maintained in an open air system can easily exchange pathogens with the environment, wild animals, or other domestic animals near the duck farm, which is consistent with the case for other livestock, such as chickens (46).…”
Section: Discussionmentioning
confidence: 48%
“…The reasons for the high prevalence (9/46 isolates [19.6%]) of ST-21 isolated from ducks in our study may be that ducks are an ST-21 host and that no large investigations have compared data for ducks with those for other poultry, such as chickens and turkeys, from the MLST database. The increasing fitness of certain STs may have induced the high prevalence in ducks, as poultry may mediate the microevolution of Campylobacter to become widespread (45). Ducks maintained in an open air system can easily exchange pathogens with the environment, wild animals, or other domestic animals near the duck farm, which is consistent with the case for other livestock, such as chickens (46).…”
Section: Discussionmentioning
confidence: 48%
“…Many reports have pointed out that the fluoroquinolone resistance emerges rapidly and persists in C. jejuni when fluoroquinolone is administered in the drinking water of broilers (McDermott et al, 2002;Luo et al, 2003;van Boven et al, 2003;Griggs et al, 2005;Humphrey et al, 2005;Takahashi et al, 2005). Moreover, fluoroquinolone-resistant strains possess an enhanced fitness in the chicken host (Luo et al, 2005;Asakura et al, 2013), and the strains were found to persist even after the selection pressure was removed (Price et al, 2005(Price et al, , 2007. Thus, these results suggest that fluoroquinolone-resistant C. jejuni strains are selected and continue to prevail following the use of fluoroquinolone in the farms.…”
Section: Discussionmentioning
confidence: 64%
“…In the present study, we isolated ST4253 strains from chickens for the first time. Asakura et al (2013) reported that fluoroquinolone-resistant ST-4526 and ST-4253 strains isolated from humans showed colonization abilities in the chicken gut that were superior to the other CC-21 strains. These results suggested that high prevalence of these STs in humans is related to their high occurrence in poultry caused by superior abilities to colonize the chicken intestine.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations